The institutional order of the welfare state and its decomposition. A perspective from the Regulation Approach - Pęciak, Renata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
This paper adopts the perspective of the French Regulation School. Regulationists assign a special role to the institutional forms in shaping the conditions of sustainable socio-economic development. The basic institutional forms refer to wage relations, competition, the role of the state, the monetary system and integration with the international system. The aim of the paper is to explain from the perspective of The Regulation Approach the conditions that made the welfare state possible, as well as the causes of its crisis. The research thesis assumes that the traditional welfare state was based on a favourable institutional order. Within this order wage relations played the most important role; the changes that occurred since the end of the 1960s made it impossible to implement the welfare state and led to the formation of a state which promotes innovation and competitiveness. The paper explains that in terms of Regulationists, the welfare state was a result of a favourable institutional system determined by wage relations. This system guaranteed the stabilization of wage compromise, strong state intervention with broad social redistribution, expansive monetary policy, competition at the national level in a stable international environment, however in conditions of low opening toward global economy. Transformations related to the process of globalization, internationalization and deepening competitiveness had undermined the Fordist mechanism which guaranteed dynamic growth and the participation of employees in the results of production. Wage relations were under the pressure of other institutional forms, especially competition, and the financial system in the 1990s. The changes in the order of institutional forms induced the evolution of the welfare state to the state which promotes innovations, new technologies and an entrepreneurial innovator.

W artykule przyjęto perspektywę francuskiej szkoły regulacji, która szczególną rolę w kształtowaniu warunków trwałego rozwoju społeczno-gospodarczego przypisuje formom instytucjonalnym. Podstawowe formy instytucjonalne odnoszą się do stosunków płacowych, konkurencji, roli państwa, systemu monetarnego oraz integracji z systemem międzynarodowym. Celem artykułu jest wyjaśnienie warunków, które pozwoliły na ukształtowanie welfare state, a także przyczyn jego kryzysu z perspektywy podejścia regulacyjnego. Przyjęta w artykule teza badawcza zakłada, że fundamentem tradycyjnego welfare state był sprzyjający układ instytucjonalny, w którym najważniejszą rolę odgrywały stosunki płacowe; zmiany, jakie się dokonały od końca lat 60. XX w. w formach instytucjonalnych uniemożliwiły realizację zasad państwa dobrobytu i doprowadziły do ukształtowania się państwa promującego innowacyjność i konkurencyjność. W artykule wykazano, iż w ujęciu regulacjonistów sukces welfare state był efektem korzystnego układu instytucjonalnego zdeterminowanego przez stosunki płacowe gwarantujące stabilność kompromisu płacowego, silną interwencję państwa z szeroką redystrybucją społeczną, ekspansywną politykę pieniężną, konkurencję realizowaną na poziomie narodowym, w stabilnym otoczeniu międzynarodowym, ale w warunkach słabego otwarcia gospodarek. Przeobrażenia związane z procesem globalizacji, umiędzynarodowienia i pogłębiania konkurencyjności podważyły mechanizm fordowski gwarantujący dynamiczny wzrost i partycypację pracowników w podziale zysków produkcyjnych. Stosunki płacowe znalazły się pod presją pozostałych form instytucjonalnych, zwłaszcza konkurencji, a w latach 90. systemu finansowego. Pod wpływem zmian w porządku instytucjonalnym państwo ewoluowało od welfare state do państwa promującego innowacje, nowe technologie i przedsiębiorczego innowatora.
Keywords: welfare state; regulation school; institution; Fordism; welfare state; szkoła regulacji; instytucje; fordyzm